Divine Callings : Understanding the Call to Ministry in Black Pentecostalism - Pitt, Richard N. (Book collections on Project MUSE., 2012)
One of the unique aspects of the religious profession is the high percentage of those who claim to be ""called by God"" to do their work. This call is particularly important within African American Christian traditions. Divine Callings offers a rare sociological examination of this markedly understudied phenomenon within black ministry. Richard N. Pitt draws on over 100 in-depth interviews with Black Pentecostal ministers in the Church of God in Christo both those ordained and licensed and those aspiringoto examine how these men and women experience and pursue ""the call."" Viewing divine call